Budidaya Ikan Lele dan Patin Guna Meningkatkan Perekonomian Melalui Program Inovasi Desa - Karin, Kharenina; Isnaeni, Nurida (Kreativasi : Journal of Community Empowerment, 2023)
The village innovation program is community development and empowerment activities carried out by students through student executives, student activity units, student associations, and student organizations. A very useful program both for advancing the village and its people, also designed as part of the implementation of the independent learning campus policy (MBKM). The ar-rahman rohis student activity unit carried out this activity in Jati Emas village, Bram Itam district, Tanjung Jabung Barat regency. The purpose of this activity is to establish a community unitary group that focuses on cultivating catfish and catfish. This program will also have a positive impact on increasing people's income and improving the welfare of local communities. The methods used are education, training, demonstrations, and mentoring for the development of fish cultivator groups in the village of jati emas. Based on the results of the activity, it is known that the involvement and participation of partners is very high in implementing the program which includes making fish feed independently, implementing good fish farming methods, and downstreaming fish farming. From the results of monitoring and evaluation activities carried out through visits to villages and through communication via whatsapp, it shows that village innovation program activities have a positive impact on partners and also villages because fish farming results can meet deficiencies in household economic need.